Anatomy of mouse recombination hot spots - Wu, Zhen K. (Oxford University Press, 2010)
Genome-wide analyses have suggested thousands of meiotic recombination hot spots across mammalian genomes. However, very few hot spots have been directly analyzed at a sub-kb scale for crossover (CO) activity. Using recombinant inbred strains as a CO library, here we report the identification and detailed characterization of seven new meiotic hot spots on mouse chromosome 19, more than doubling the number of currently available mouse hot spots. Although a shared feature is the narrow 1.5–2.5-kb width of these recombinogenic sites, these analyses revealed that hot spots have diverse sequence attributes and distinct symmetric and asymmetric CO profiles. Interestingly, CO molecules with discontinuous conversion tracts are commonly observed, contrasting with those found in human. Furthermore, unlike human hot spots, those present in the mouse do not necessarily have a quasi-normal CO distribution but harbor CO repulsion zones within recombinogenic cores. We propose a model where local chromatin landscape directs these repulsion zones.